Meat Quality on Sentul Cocks with Different Immunoglobulin Yolk Concentrations - Ria Ariyanti; N Ulupi; T Suryati; RI Arifiantini (Jurnal Ilmu Ternak dan Veteriner, 2019)
Sentul cocks is one of the native chicken breeds in Indonesia which is originally raised by Villagers in Ciamis District, West Java. Healthy chicken cells can function properly, especially in the metabolic process. Healthy chickens are expected to produce better muscle development. IgY is a protein molecule substance that can neutralize a number of microorganisms that cause infection. The purpose of this study was to evaluate the effect of IgY concentration on physicochemical and organoleptic qualities of meat. This study used 20 cocks,  4th month ages, consist of 2 treatments (IgY concentrations above 9.30 ± 0.45 mg mL-1 and IgY concentrations below 9.30 ± 0.45 mg mL-1). The variable observed include physicochemical and organoleptic quality of meat. The study was used completely randomized design. Data were analyzed by t-test. The result concluded that cocks with concentrations above 9.30 ± 0.45 mg mL-1 produced meat with lower malonaldehyde. The low content of malonaldehyde in meat shows that the meat produced is healthier.